(untitled) (Journal of Parents and Teachers, 2026)
It is a fact, as the author states, that there is a growing desire for greater participation within the school environment among all members of the educational community. For this reason, a questionnaire on a Headteacher’s Participatory Decision-Making is proposed, which can be administered in each school to identify the leadership style in place. The questionnaire consists of 10 statements representing steps in the decision-making process; these do not necessarily have to follow the proposed order, nor do they all have to be included – it is flexible to suit the reality of each school.